Beneficial effect of lixisenatide after 76 weeks of treatment in patients with type 2 diabetes mellitus: A meta‐analysis from the GetGoal programme. Issue 2 (8th December 2016) - Broglio, Fabio; Mannucci, Edoardo; Napoli, Raffaele; Nicolucci, Antonio; Purrello, Francesco; Nikonova, Elena; Stager, William; Trevisan, Roberto
Abstract : Aims: To evaluate the long‐term efficacy and safety of lixisenatide, a short‐acting, prandial glucagon‐like peptide‐1 receptor agonists (GLP‐1 RA) as add‐on therapy in type 2 diabetes mellitus. Methods: A meta‐analysis of 76‐week results of 5 placebo‐controlled clinical trials from the GetGoal programme was performed, including 3000 inadequately controlled adult diabetic patients where lixisenatide 20 µg once‐daily was administered in combination with metformin (GetGoal‐M and GetGoal‐F1), sulphonylurea ± metformin (GetGoal‐S), basal insulin ± metformin (GetGoal‐L) or pioglitazone ± metformin (GetGoal‐P). Results: A significant reduction in HbA1c at 76 weeks was observed in the intervention arm compared to placebo (LSM difference: −0.41%, 95%CI: −0.51, −0.32, P < .00001). Compared to placebo, lixisenatide induced a larger decrease in fasting plasma glucose (LSM difference −0.49 mmol/L, 95% CI −0.71, −0.27, P < .0001) and postprandial glucose excursion after a standard test meal (LSM difference −3.29 mmol/L, 95% CI −4.17, −2.42, P < .00001). A bodyweight reduction was observed in the lixisenatide arm (LSM difference −0.40 kg, 95%CI: −0.8, −0.01, P = .05). The risk of hypoglycaemia was slightly higher with lixisenatide vs placebo (risk difference +0.02, 95% CI: 0, 0.04, P = .04). The most commonly observed non‐severe adverse events were nausea and vomiting, which after week 16 and week 8, were steadily <4% and <1% in the lixisenatide arm, respectively. Conclusions: Lixisenatide, a once‐daily prandial GLP‐1 RA, provides long‐term glycaemic control, a sustained beneficial effect on weight and with a good safety profile.